From Community College to University: A Personal Commentary on the Evolution of an Institution - Dennison, John D. (Canadian Journal of Higher Education, 2006)
This paper documents the development of a unique institution in Canadian higher education, the university college in British Columbia. From its roots as a comprehensive community college, the university college was confronted with numerous legislative and policy changes which culminated in its current claim to be called a regional university. In support of this assertion, a number of issues are addressed, including the role and mandate of the university college, academic freedom and tenure, governance, administration, and the legal status under which it was constituted. Over a period of 15 years the university college underwent an organizational evolution as remarkable as it was unprecedented.